Comparative Efficacy of Antrodia cinnamomea on Liver Function Biomarkers in Mice and Rats: A Network Meta-Analysis - Chien-Liang Kuo; Berne Ting; Ray Jui-Hung Tseng; Shih-Ping Liu; Jun-Yang Liou (Antioxidants)
This study systematically evaluates the hepatoprotective effects of different types and doses of Antrodia cinnamomea extracts (triterpenoids, polysaccharides, and ubiquinone derivatives) on liver function biomarkers, including alanine aminotransferase (ALT), aspartate aminotransferase (AST), malondialdehyde (MDA), and tumor necrosis factor-alpha (TNF-α), using a network meta-analysis (NMA) approach. Comprehensive literature searches were conducted in PubMed, Embase, Cochrane CENTRAL, and Web of Science databases to identify eligible animal studies involving standardized mouse and rat models. Interventions were categorized based on extract types and dosage levels (high, medium, low), with controls including negative groups (vehicle-treated) and positive groups (e.g., silymarin, N-acetylcysteine). A random-effects model estimated mean differences (MDs) with 95% confidence intervals (CIs), risk of bias was assessed with the SYRCLE tool, and sensitivity analyses verified robustness. The protocol has been registered in INPLASY (INPLASY202540040). The results indicated that triterpenoids, particularly at high and medium doses, were the most effective in reducing ALT (MD: −42.37, 95% CI: −54.19 to −30.54) and AST (MD: −50.18, 95% CI: −73.31 to −27.05). High-dose polysaccharides also showed notable effects, while other interventions demonstrated variable efficacy. For oxidative stress, high-dose triterpenoids showed the most pronounced reduction in MDA (MD: −19.05, 95% CI: −24.00 to −14.09), followed by medium-dose triterpenoids and all-dose polysaccharides. Regarding inflammation, high- and medium-dose triterpenoids significantly reduced TNF-α levels (high-dose MD: −88.75, 95% CI: −119.68 to −57.82; medium-dose MD: −89.27, 95% CI: −125.51 to −53.02), with overlapping confidence intervals indicating similar efficacy. High- and low-dose polysaccharides also demonstrated moderate anti-inflammatory effects. In conclusion, high-dose triterpenoids showed favorable and consistent effects across multiple biomarkers, which highlights their potential value for future liver-related therapeutic strategies.